The relative impact of underweight, overweight, smoking, and physical inactivity on health and associated costs in Indonesia: propensity score matching of a national sample - Zulfikar Ihyauddin; Tiara Marthias; Kanya Anindya; Nawi Ng; Fatwa Sari Tetra Dewi; Emily S. G. Hulse; Reza Pandu Aji; Dwi Astuti Dharma Putri; John Tayu Lee (BMC, 2022)
Abstract Background Indonesia is in the middle of a rapid epidemiological transition with an ageing population and increasing exposure to risk factors for chronic conditions. This study examines the relative impacts of obesity, tobacco consumption, and physical inactivity, on non-communicable diseases multimorbidity, health service use, catastrophic health expenditure (CHE), and loss in employment productivity in Indonesia. Methods Secondary analyses were conducted of cross-sectional data from adults aged ≥ 40 years (n = 12,081) in the Indonesian Family Life Survey 2014/2015. We used propensity score matching to assess the associations between behavioural risk factors and health service use, CHE, employment productivity, and multimorbidity. Results Being obese, overweight and a former tobacco user was associated with a higher number of chronic conditions and multimorbidity (p < 0.05). Being a former tobacco user contributed to a higher number of outpatient and inpatient visits as well as CHE incidences and work absenteeism. Physical inactivity relatively increased the number of outpatient visits (30% increase, p < 0.05) and work absenteeism (21% increase, P < 0.06). Although being underweight was associated with an increased outpatient care utilisation (23% increase, p < 0.05), being overweight was negatively associated with CHE incidences (50% decrease, p < 0.05). Conclusion Combined together, obesity, overweight, physical inactivity and tobacco use contributed to an increased number of NCDs as well as medical costs and productivity loss in Indonesia. Interventions addressing physical and behavioural risk factors are likely to have substantial benefits for individuals and the wider society in Indonesia.